Architecturing materials at mesoscale: some current trends. Issue 10 (3rd October 2021) - Estrin, Yuri; Beygelzimer, Yan; Kulagin, Roman; Gumbsch, Peter; Fratzl, Peter; Zhu, Yuntian; Hahn, Horst
Abstract : This article overviews several areas of research into architectured materials which, in the opinion of the authors, are most topical and promising. The classes of materials considered are based on meso scale designs inspired by animate and inanimate Nature, but also on those born in the minds of scientists and engineers, without any inspiration from Nature. We present the principles governing the design of the emerging materials architectures, discuss their explored and anticipated properties, and provide an outlook on their future developments and applications. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: The article addresses several hot topics with a great promise for innovative materials design.